2020
DOI: 10.14198/jhse.2021.162.17
|View full text |Cite
|
Sign up to set email alerts
|

Personal characteristics supporting Paralympic athletes’ self-realization in sports

Abstract: The purpose of this study was to investigate the personal characteristics supporting Paralympic athletes' selfrealization in sports. The study involved 106 members of the Paralympic and Deaflympic teams of Ukraine (16-53 year-old, the average age of 28.3 ± 7.2 years; 84 men with the average age of 27.7 ± 6.7 years and 22 women with the average age 30.3 ± 8.3 years) in different sports (football, fencing, power-lifting, sitting volleyball, judo, canoeing in pairs, swimming). It is determined that the most impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Through the systematic review process, we identified twenty-seven studies: twelve from Europe (Italy [66,79], Ireland [68], UK [59,63,78,80], Poland [7], Portugal [74], Turkey [65] and Ukraine [69,70]), ten from North America (USA [47,60,72,73,[81][82][83] and Canada [64,67,75], three from South America (Brazil [61,62] and Chile [77]), one from Asia (Indonesia [76]) and one from Oceania (Australia [71]).…”
Section: Originmentioning
confidence: 99%
“…Through the systematic review process, we identified twenty-seven studies: twelve from Europe (Italy [66,79], Ireland [68], UK [59,63,78,80], Poland [7], Portugal [74], Turkey [65] and Ukraine [69,70]), ten from North America (USA [47,60,72,73,[81][82][83] and Canada [64,67,75], three from South America (Brazil [61,62] and Chile [77]), one from Asia (Indonesia [76]) and one from Oceania (Australia [71]).…”
Section: Originmentioning
confidence: 99%
“…According to both participants, this life goal can produce extraordinary rewards, where these rewards can later help their family's lives because individual economic factors play a very important role in individual psychological wellbeing. The positive impact of sport on people with disabilities consistently influences psychological well-being and can change lives for the more positive (Haslett et al, 2017;Kane et al, 2016;O. Kokun et al, 2021;O.…”
Section: Discussionmentioning
confidence: 99%
“…This technique allows a researcher to quickly and accurately evaluate various components of psychological state (by choice of the researcher). In particular, the scale has been demonstrated to be effective in investigating a person's psychological state while operating in complex and extreme conditions (Kokun & Bakhmutova, 2020;Kokun et al, 2021). It is also important that this technique allowed us to evaluate deployment-specific indicators.…”
Section: Methodsmentioning
confidence: 99%